2015
DOI: 10.1089/end.2014.0401
|View full text |Cite
|
Sign up to set email alerts
|

The SimPORTAL Fluoro-Less C-Arm Trainer: An Innovative Device for Percutaneous Kidney Access

Abstract: The fluoroscopy-less CAT is an economically feasible and accurate model for training parallax. It effectively replicates the functions of a C-arm X-ray system for percutaneous access to the kidney without any radiation exposure to the learner. Further studies will examine construct validity for training and assessing percutaneous access skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…22 Other nonbiological bench models used prototyping or 3D printing. [23][24][25][26] Only one study reported the use of anesthetized live pigs as module 1 of the Modular Training Scheme, which included renal puncture, tract dilatation using the Amplatz dilators, and orientation with the nephroscope in a live pig. 27 The PERC MentorÔ (Simbionix, Cleveland, OH) was the only VR simulator that has been validated for training and assessment of PCA skills.…”
Section: Resultsmentioning
confidence: 99%
“…22 Other nonbiological bench models used prototyping or 3D printing. [23][24][25][26] Only one study reported the use of anesthetized live pigs as module 1 of the Modular Training Scheme, which included renal puncture, tract dilatation using the Amplatz dilators, and orientation with the nephroscope in a live pig. 27 The PERC MentorÔ (Simbionix, Cleveland, OH) was the only VR simulator that has been validated for training and assessment of PCA skills.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [19] used a novel kidney system made of silicone. Veneziano et al [20] and Turney [21] advocated a novel 3D-printed model of the pelvicalyceal system for puncture.…”
Section: Discussionmentioning
confidence: 99%
“…In three cases [Vesicourethral anastomosis (VU trainer), the C-arm percutaneous access trainer (CAT), and vascular control models], this process was done through private interviews in series with several individual expert endourologists without group discussion/consensus. 7 Reference anatomy was obtained from Dicom images that were translated into a deformable MESH in Maya (Autodesk, Inc., San Rafael, CA) by a digital artist (Dan Burke). For physical models [kidney ureter (KU), kidney ureter bladder (KUB), BLUS arteries, NLM, Pyeloplasty, VU model, vascular control models, and the CAT], the Maya model was translated into Solid Works (Dassault Systemes, Concord, MA) as a computer-assisted model (CAM) for 3D printing/ sculpting as either a negative space to mold materials around or a ''casted'' anatomic structure.…”
Section: Methodsmentioning
confidence: 99%
“…For physical models [kidney ureter (KU), kidney ureter bladder (KUB), BLUS arteries, NLM, Pyeloplasty, VU model, vascular control models, and the CAT], the Maya model was translated into Solid Works (Dassault Systemes, Concord, MA) as a computer-assisted model (CAM) for 3D printing/ sculpting as either a negative space to mold materials around or a ''casted'' anatomic structure. [5][6][7][8][9] In the case of a dynamic virtual model, such as the GL Sim, the deformable meshes of anatomy were textured to match important visual cues and directly imported into the virtual scene. 3 For pyeloplasty, CAT, KU/KUB, and vascular control models, where tissue-tool interactions were important, studies were performed on, or referenced from, fresh cadaveric tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation